Krisis Keamanan Negara Haiti: Analisis Konstruktivisme terhadap Failed State dalam Melawan Kekuatan Kelompok Bersenjata - Doril Wirli Septriel; Atika Puspita Marzaman (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
This article analyzes the security crisis in Haiti through the lens of constructivist theory in International Relations. Haiti represents one of the clearest examples of a failed state in the Western Hemisphere, where state authority has collapsed and been replaced by armed criminal groups known as gangs. Using a constructivist perspective, this article traces how social constructions, identities, and historically formed norms have shaped the fragility of the Haitian state. The study also integrates the concept of human security to illustrate the real impact of this crisis on citizens' security across seven dimensions: economic, food, health, environmental, personal, community, and political. The main finding suggests that Haiti's state failure is not merely a product of weak formal institutions, but the result of a long process of social construction, encompassing the legacy of colonialism, crippling reparation payments, counterproductive foreign intervention, and the normalization of violence in everyday life. From a constructivist perspective, restoring security in Haiti requires narrative reconstruction, rebuilding social trust, and comprehensive reform of institutional norms.